Pengaruh Kondisi Kultur Terhadap Karakteristik Selulosa Bakterial dari Air Kelapa Sebagai Membran untuk Filtrasi Methylene Blue - Deby Febrianty Isba Diputri; Muhammad Hammam Zufar Annafie; Ari Tri Marwanto; mutiara, tintin (Chemistry Department, Universitas Islam Indonesia, 2024)
The development of the industries affected the increase of wastewater discharged into the environment. Dye is a pollutant that is quite dangerous for human health and ecosystems. Recently, various methods have been found to treat dyes from wastewater. Ultrafiltration wastewater treatment is one method that has minimal weaknesses. Bacterial cellulose is a promising biopolymer for separation processes due to its biocompatibility. This study applied various culture conditions to determine the optimum ones to produce bacterial cellulose membranes. The resulting B4 membrane has the best MB solution filtration capability, with a %removal value of 73.24%.